2013
DOI: 10.1017/s1751731113000608
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of entire male pigs is improved by socialising piglets and keeping intact groups until slaughter

Abstract: In today's production systems, pigs raised for slaughter are mixed many times, resulting in stress and fighting. The negative consequences of mixing are probably more severe with entire males than with castrates, as they fight more. In this project, we studied a system without castration where entire male pigs met unfamiliar pigs only once. Piglets from two litters were allowed to visit each other from circa 2 weeks of age through an opening between the farrowing pens. Entire males from these litters were kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
1
22
1
3
Order By: Relevance
“…This is in agreement with Fàbrega et al (2013), who also found more skin lesions in mixed groups compared with stable wean-to-finish groups. In this study, all pigs had been able to socialise with other litters before weaning, which was also the case for the unmixed group in the study by Rydhmer et al (2013).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…This is in agreement with Fàbrega et al (2013), who also found more skin lesions in mixed groups compared with stable wean-to-finish groups. In this study, all pigs had been able to socialise with other litters before weaning, which was also the case for the unmixed group in the study by Rydhmer et al (2013).…”
Section: Introductionmentioning
confidence: 64%
“…As regards mounting behaviour, Rydhmer et al (2013) found more mounting in the intact groups at start and end of the study, whereas Fàbrega et al (2013) found no effect on mounting behaviour in a stable wean-to-finish system compared with mixed groups.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Animals and sampling A total of 46 entire male pigs of Swedish Yorkshire were recruited from a study on welfare of entire male pigs in relation to socializing piglets, and keeping intact groups until slaughter (Rydhmer et al, 2013). The animals were born and raised at the Swedish Livestock Research Center in Uppsala in accordance with Swedish regulations for use of pigs.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were, therefore, randomly sampled from the two strata into the subsets used in the present study. Details on management of pigs are documented elsewhere (Rydhmer et al, 2013).…”
Section: Methodsmentioning
confidence: 99%